EVALUASI KEBIJAKAN PENGELOLAAN PARKIR Studi Kasus: Kota Semarang - Hendrawan Toni Taruno (Universitas Sultan Ageng Tirtayasa, 2017)
This research aimed to discuss the parking policy in Semarang which has not been managed properly. In general, the condition of parking management in Semarang is still quite bad. This is indicated by the poor parking service provided and the low amount of parking retribution every year. During 2011 - 2012 for example, the revenue realization of parking retribution was only about 1.3 billion rupiah from the target of about 4.8 billion rupiah, or only about 25 percent of the target set. This condition was worsened by parking services that were very uncomfortable and unsatisfactory. This research used a descriptive method with a qualitative approach. The author used secondary data which was obtained from PATTIRO Kota Semarang. This study focuses on parking policy in Semarang by describing the condition of parking management which already exists and discussing revenue gap between target and realization from parking retribution. By analizing data, the authors argued that the main problem of parking management in Semarang is the weak implementation of the Regional Regulation on parking retribution. In addition, the parking policy managed by local Government tends to be unsatisfactory, potentially leaky, and the realization is far from the target set. Therefore, in order to solve the parking problems, the local Government must seriously implement the local regulation of parking retribution and rearrange the parking management which already exists.